A comparison of general aviation accidents involving airline pilots and instrument-rated private pilots. (February 2021) - Boyd, Douglas D.; Scharf, Mark; Cross, David
Highlights: Lower proportion of airline pilot fatal accidents due to in-flight loss-of-control. Dis-proportionate count of ground loss-of- control mishaps for airline pilots. Loss of ground directional control reflected a preference for tail-wheel aircraft. Airline pilot mishaps over-represented for those below legal minimum altitudes. Abstract: Introduction: The extremely low accident rate for U.S air carriers relative to that of general aviation (∼1 and ∼60/million flight hours respectively) partly reflects advanced airman certification, more demanding recurrency training and stringent operational regulations. However, whether such skillset/training/regulations translate into improved safety for airline pilots operating in the general aviation environment is unknown and the aim of this study. Methods: Accidents (1998–2017) involving airline pilots and instrument-rated private pilots (PPL-IFR) operating non-revenue light aircraft were identified from the NTSB accident database. An online survey informed general aviation flight exposure for both pilot cohorts. Statistics used proportion testing and Mann-Whitney U tests. Results: In degraded visibility, 0 and 40% ( χ 2 p = 0.043) of fatal accidents involving airline and PPL-IFR airmen were due to in-flight loss-of-control, respectively. For landing accidents, airline pilots were under-represented for mishaps related to airspeed mismanagement ( p = 0.036) relative to PPL-IFR but showed a dis-proportionate count (2X) of ground loss-of-directional control accidents ( p = 0.009) the latter likely reflecting a preference for tail-wheel aircraft. The proportion of FAA rule violation-related mishaps by airline pilots was >2X (7 vs. 3%) that for PPL-IFR airmen. Moreover, airline pilots showed a disproportionate ( χ 2 p = 0.021) count of flights below legal minimum altitudes. Not performing an official preflight weather briefing or intentionally operating in instrument conditions without an IFR flight plan represented 43% of airline pilot accidents involving FAA rule infractions. Conclusions: These findings inform safety deficiencies for: (a) airline pilots, landing/ground operations in tail-wheel aircraft and lack of 14CFR 91 familiarization regulations regarding minimum operating altitudes and (b) PPL-IFR airmen in-flight loss-of-control and poor landing speed management. Practical Applications: For PPL-IFR airmen, training/recurrency should focus on unusual attitude recovery and managing approach speeds. Airline pilots should seek additional instructional time regarding landing tail-wheel aircraft and become familiar with 14CFR 91 rules covering minimum altitudes.